CONDUCTING CONTROL TESTS OF 11-13-YEAR-OLD FOOTBALL PLAYERS IN MULTI-YEAR TRAINING STAGES (for example, starting speed) (TAMADDUN NURI JURNALI, 2024)
The article examines the training of football players, conducts research on the organization of complex training of football players at the stages of long-term training, as well as testing of players who regularly engage in long-term training. studied in detail. The aspects that should be paid attention to when testing various qualities of players aged 11-13 are studied. The results of control tests were statistically analyzed and conclusions were made.